2017
DOI: 10.1186/s12987-017-0073-2
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of CSF flow using phase-contrast MRI with ventriculomegaly and CSF opening pressure in mucopolysaccharidoses

Abstract: BackgroundVery little is known about the incidence and prevalence of hydrocephalus in patients with mucopolysaccharidoses (MPS). The biggest challenge is to distinguish communicating hydrocephalus from ventricular dilatation secondary to brain atrophy, because both conditions share common clinical and neuroradiological features. The main purpose of this study is to assess the relationship between ventriculomegaly, brain and cerebrospinal fluid (CSF) volumes, aqueductal and cervical CSF flows, and CSF opening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We sought to determine whether we could detect alterations in a marker of neuronal degeneration neurofilament light chain (Nf-L), in this nMPS II patient population. As mentioned above, there is significant neurodegeneration in nMPS II patients, as observed via TUNEL staining of post-mortem brain tissue or MRI methods in living patients [ 17 , 18 , 19 ]. However, no fluid-based biomarker for monitoring neurodegeneration in nMPS II patients has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to determine whether we could detect alterations in a marker of neuronal degeneration neurofilament light chain (Nf-L), in this nMPS II patient population. As mentioned above, there is significant neurodegeneration in nMPS II patients, as observed via TUNEL staining of post-mortem brain tissue or MRI methods in living patients [ 17 , 18 , 19 ]. However, no fluid-based biomarker for monitoring neurodegeneration in nMPS II patients has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…While MRI imaging studies and post-mortem analysis of brain tissue show clear neurodegeneration in nMPS II [ 17 , 18 , 19 ], there are currently no reports of markers of neurodegeneration in biofluids from nMPS II patients. Neurofilament light chain (Nf-L), a structural protein of the neuronal cytoskeleton, is a reliable biomarker of axonal injury and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[118][119][120][121][122] In fact, NPH patients show significantly elevated PSV, peak mean velocity, and stroke volume values. 118 On the other hand, using PC-MRI and measurements of CSF volumetrics (mucopolysaccharidoses [MPS]), 123 it has been demonstrated that individuals with MPS exhibit connections between CSF flow measures. When a ventricular shunt is suspected of malfunctioning, CSF flow assessed by PC-MRI within the parenchymal section may accurately reveal the shunt's functional condition.…”
Section: Pc-mri In Neurological Conditionsmentioning
confidence: 99%
“…More recent studies are showing the CSF current changes made by PC-MRI in diseases such as idiopathic intracranial hypertension, neuro-Behçet disease, amyotrophic lateral sclerosis, and mucopolysaccharidoses [6][7][8][9]. In the relevant literature, the link between CSF pressure and body mass index (BMI) was examined; however, no studies were published on the relationship between CSF flow dynamics, BMI, and head circumference (HC) [10].…”
Section: Introductionmentioning
confidence: 99%